External Competition Strategy Analysis And Blue Ocean Strategy Using Strategy Management Approaches - Rianita Puspa Sari; Ajeng Alaya Putri; Azri Maya Monica (Relevance: Journal of Management and Business, 2020)
The culinary industry contributes to the development of MSMEs in the country and requires companies to be able to increase their competitiveness, the need for a strategic management approach so that MSMEs can be competitive. Strategy formulation is used by reviewing MSMEs using the PESTLE analysis method for external environmental analysis, competitiveness analysis using the Five Force method, Ansoff Matrix method to determine market development strategies at the business unit level and Blue Ocen Strategy to determine strategies in winning the market. Data collected through interviews and observations. The results obtained show that F&B MSMEs can implement market penetration strategies by creating online stores and websites. Market development strategies can be done through Healthy Store, Retailer and consignment. Product development strategies by creating healthy subscription and journal packages, and diversifying by conducting Healthy Sessions or Workshops. From the four methods above and alternative solutions offered, it can be concluded that the most appropriate strategy to improve competitiveness is to diversify in the form of a Healthy Session or Workshop.